Hubungan Tingkat Pengetahuan dan Tingkat Kecemasan Menghadapi Masa Menopause - Panjaitan, Tiffara Keavy Sharon; Haro, Masta (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research intends to identify the relationship between the level of knowledge and women's anxiety about facing menopause among women in the Seventh-day Adventist Church Salemba, Central Jakarta. The Method that has been used in this is descriptive quantitative, with a correlative approach to analyze the relationship between the level of knowledge and the level of anxiety that has been measured by a knowledge questionnaire and the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire. The results of the research showed that there was a relationship between the level of knowledge and the level of anxiety facing the menopause at the Seventh-day Adventist Church Salemba, Central Jakarta. Keywords: Anxiety, Menopause, Knowlege level